Community management or coproduction? The role of state and citizens in rural water service delivery in India - Hutchings, Paul (Water Alternatives Association, 2018)
This paper makes the case for a realignment in the discourse and conceptualisation of community management of rural water supply. It draws on data from 20 case studies of reportedly successful community management programmes from India to argue that current discourse is remiss not to describe the substantial role of the state and other supporting agencies in financing and supporting service provision. In the context of such substantial levels of support, conceptually, it is argued that the tendency to treat the challenge of rural water supply as one of either a community participation or collective action problem that only the community can address further limits current thinking in this area. Recasting the primary challenge of rural water service delivery as improved cooperation and coordination between state and citizen, the paper proposes a more substantial focus on coproduction as a route to overcome sustainability problems in rural water supply. The paper ends by reflecting on the generalisability of this thinking noting the specific context of the Indian empirical data. It concludes by arguing that, although certain aspects of the study are specific to that empirical domain, the normative and conceptual reasons for shifting the discourse remain applicable in broader contexts.
Keywords: Community management; Coproduction; Rural water supply; India